Evaluation Of Nearly Zero Energy Residential Buildings Design Strategies In Three Climatic Zones In Jordan - Ibrahim, Anwar; Ali, Hikmat; Rasheed, Razan (International Journal of Energy Economics and Policy, 2022)
Designing zero or near zero-energy residential buildings will considerably help in reducing the general energy consumption. Geographically, Jordan retains three different altitude zones with unique climatic conditions for each which imperatively entails deploying different approaches to attain near zero-energy houses. This study aims to investigate the best economic feasible design strategies that possibly lead to near zero-energy residential buildings. Based on the most common detached house design-layout and materials on each zone, three case study houses were designed. The research methodology was based on three levels of efficiency. By using Design Builder, each efficiency level was examined by three design strategies: passive, active, and renewable energy design strategies in order to improve the energy performance of the buildings. The results showed that implementing the three levels concurrently would result in achieving the nearly zero-energy houses with efficient cost and less than 10 years payback period. In the high-land altitude zone, the annual consumption of power was reduced from 79.1 kwh/m2 to -13.6 kwh/m2. For the medium altitude zone, the annual consumption dropped down from 78.8 kwh/m2 to -16.5 kwh/m2. Finally, the annual consumption of electricity in the low-latitude zone decreased from 75.7 kwh/m2 to -21.1 kwh/m2.